An investigation of gram-positive pathogens in powdered foods - Swift, Benjamin (2010)
The purpose of the project was to obtain and test a range powdered food products that are marketed for consumption by individuals that may be immunocompromised. Hence seventeen infant formula milks (0-6months), twelve over-the-counter, elderly, build-up products and nineteen sports powdered protein shakes were examined. These products were tested for the presence of four different Gram-positive pathogens: Two spore formers; Bacillus cereus and Clostridium perfringens and two non-spore formers; Listeria monocytogenes and Staphylococcus aureus. Products were tested according to the ISO standardised methods of testing for described for each of the organisms and samples plated on different diagnostic agars. The presumptively positive organisms that formed characteristic colonies were then further identified. This identification was confirmed in two ways; biochemically, using a wide range of tests including API, and molecularly using PCR-based assays. The results from the project showed that from the 48 products tested; 16 contained B. cereus, nine S. aureus, three L. monocytogenes and one with C. perfringens. To further investigate whether the non-spore forming organisms that survived in these products were more resilient than expected, a heat inactivation experiment was carried out. A simulated high-temperature-short-time (HTST) pasteurisation was set up and the results gained suggested that the S. aureus isolate was able to survive pasteurisation but not subsequent cold and heat shock. In contrast the L. monocytogenes was sub-lethally damaged by the heat treatment but then recovered during cold storage. Thus postulations about how or where these organisms entered food could be made.